(untitled) (مجلة ديالى للبحوث الانسانية, 2025)
Various cultures, such as Arab and American, have developed between myth, literature, and religion. The employment of myths in works of literature of both cultures is the most visible manifestation of this trend. In addition to that, religion plays an important role to shape the myths of the old nations. The theme "Myth, Religion and Literature" examines the mythological origins of literature. It covers academics who postulate the patterns they identified in hero tales and the patterns themselves. Myths as a whole are too diverse to be able to have a similar narrative. However, standard plots have been suggested for particular types of religious stories, most often for hero myths. Some other types of myths, such as creation myths, flood myths, paradisiacal myths, and future myths, have proven to be too diverse to be useful for anything more than the most broad-brush comparisons.